Knowledge and adherence to the Mediterranean diet in individuals practicing regular amatorial physical activity: a cross-sectional study conducted in the Metropolitan Area of Palermo, Italy - Costantino, Claudio; Casuccio, Alessandra; Belluzzo, Miriam; Balsamo, Francesco; Bonaccorso, Nicole; Carubia, Alessandro; D’Azzo, Luciano; Gattuso, Luisa; Lo Porto, Maria Chiara; Sciortino, Martina; Vitello, Tania; Tabacchi, Garden; et al. (Frontiers in Public Health, 2023)
Mediterranean Diet (MD) is a universal model of nutrition that prevents several metabolic, cardiovascular, and oncological diseases. Main objective of the present study was to analyze adherence and knowledge regarding MD principles in a sample of individuals practicing amatorial sports from the Metropolitan Area of Palermo. To this end, a cross-sectional study was conducted in 10 Sports Centers, between October 2020 and September 2021, through a previously validated anonymous questionnaire structured in 5 sections including 74 items. Overall, 337 subjects answered to the questionnaire. Based on the multivariable analysis conducted, a higher knowledge score (KS) on MD principles was observed among individuals daily consuming vegetables (OR: 3.32; CI95%: 1.82-6.02) and in the ones more adherent to MD principles (OR: 10.15; CI95%:5.47-18.85). More in depth, using MEDAS score to analyse the adherence to MD, a significant lower adherence was observed among overweight/obese (OR: 0.57; CI95%:0.33-0.99) and among employed subjects (OR: 0.52; IC95%: 0.28-0.98); while, a higher adherence was highlighted among daily consumers of vegetables (OR: 2.52; CI95%:1.52-4.17), daily consumers of fruit (OR: 1.77; CI95%:1.08-2.90) and in individuals that have daily breakfast (OR: 4.29; CI95%:1.15-15.96). In accordance with the WHO Europe Gaining Health Campaign, Public Health Authorities should simplify accessibility to healthy food among general population, promoting principles and accessibility to MD.